An identification guide to some major Quaternary fossil reef‐building coral genera (Acropora, Isopora, Montipora, and Porites). (5th November 2014) - Humblet, Marc; Hongo, Chuki; Sugihara, Kaoru
Abstract Fossil coral identification is essential for paleoenvironment and sea level reconstructions and in paleoecological and evolutionary studies. It follows the taxonomy of their modern analogues and therefore is based on the external skeleton macromorphology. However, for geologists examining outcrops or drill cores, identification largely relies on cross sections. The coral surface is usually obscured by encrusters or by sediments, or because corals are broken or eroded. It is therefore important to understand the relationship between the internal structure of corals and their surface morphology. We provide a comprehensive description of the internal structure of four common coral genera (Acropora, Isopora, Montipora, and Porites). This identification guide is addressed to reef geologists who wish to identify Quaternary reef corals at the generic level based on cross sections. The massive basal part of Acropora is composed of an interbranch space filled with a highly regular mesh‐like network of skeletal elements parallel and perpendicular to growth direction. Corallites have conspicuous dissepiments with a ladder‐like appearance in longitudinal section. Corallites of Isopora are structurally similar but they do not show the same differentiation into axial and radial corallites. Corallites are generally sinuous and the coenosteum is less regular. Montipora has smaller corallites which appear as tubes lined with spiny septa. The coenosteum is characterized by long rod‐like skeletal elements parallel to growth direction projecting upward at the colony surface to form spinules or larger ornementations. These vertical rods are connected laterally by short bar‐like skeletal elements. In Porites, the size of corallites is similar to Montipora but they are juxtaposed and completely filled with skeletal elements. Longitudinal cross sections display a dense network of corallites' skeletal components parallel and perpendicular to growth direction. This new taxonomic guide provides a useful reference material for those who attempt to identify reef‐building corals in the fossil record.